Enhancement Of Microalgae Adhesion To Substrate Via Algal Organic Matter Pre-Treatment - Lew, Jun Kit (Universiti Sains Malaysia, 2021)
Porous substrate cultivation (PSC) is more advantageous than the conventional suspension cultivation in terms of the reduction of water volume needed and the omission of gas-liquid mass transfer resistance. Thus, the degree of adhesion of Amphora coffeaeformis, Cylindrotheca fusiformis and Navicula incerta on commercial polyvinylidene fluoride (PVDF) membrane strip surface before and after coating with the soluble extracellular polymeric substances (sEPS) of N. incerta was determined in this study. All three species showed stronger cell adhesion on the coated PVDF membrane strips than on the pristine ones. This was because the coated PVDF membrane strips already had a conditioning film on its surface after the coating while the pristine membrane strips only had biofilms start developing on them when the experiment started. The sEPS generally had higher productivity of polysaccharide than of protein while for bounded EPS (bEPS), the productivities of polysaccharide and protein between pristine and coated membrane strips were compared. All three microalgal species on pristine membrane strips produced bEPS that contained higher protein content than polysaccharide whereas on coated membrane strips, the productivity of bEPS polysaccharide was higher than that of protein for A. coffeaeformis and C. fusiformis and this result was related to the species’ adaptation to the substrate surface wettability. However, N. incerta did not show such relation maybe because it had a stable, yet low metabolic rate on the coated membrane strips, so extracellular enzymes were secreted to compensate the low rate, leading to a higher protein productivity.